Élite Sport & Identity Transitions: A Qualitative Study on a World Class Trampoline Gymnast - Sergio Bellantonio (Pensa MultiMedia, 2022)
Identity transitions out of sport represent a still unexplored research interest in pedagogy, even if identity and related existential crises has been well studied by the pedagogical literature in recent decades, thanks to the postmodern condition that has also loaded of seriousness individual and collective choice and guidance processes. Identity crisis and personal and professional existential redefinitions were just some of the issues that pedagogy intended to investigate. Among these, however, the sports context still seems to be relegated to the margins. If sport is to be considered a context with a high emotional-affective impact for athletes who live it from a young age, what happens when an élite athlete decides, voluntarily or not, to abandon sports career? What scenarios are envisioned and what opportunities are granted to athletes? To analyze the phenomenon in depth, a case study on a world class trampoline gymnast was conduct, using narrative inquiry. The qualitative research followed the athlete's identity transition out of sport process at the end of his sports career over 36 months, during which semi-structured interviews were conducted. This allowed us to reconstruct the processuality of the phenomenon, through a conceptual network that emerged from data analysis thanks to ATLAS. ti 6.0 software.